Asymmetric information and daily stock prices in Brazil. (2020)
This paper has the goal of analyzing the association between asymmetric information, measured by Corwin-Schultz bid ask spread estimator, and stock prices in the Brazilian stock market. Daily data from 64 corporations over a period of 10 years were examined using the Johansen-Fisher panel cointegration technique in order to assess the validity of asymmetric information measurements in shorter periods than in previous studies. The results indicate that asymmetric information anticipates stock prices over a period of up to two days in a theoretically consistent way. Future research may control the results via traditional finance variables.